Analysis on the Meshing Performance of Modified Involute Enveloping Toroidal Worm Transmission Based on Medium Gears - Chen Yan; Ye Qiang; Zhao Liangliang; Yan Lei; Chen Yonghong (Jixie chuandong, 2024)
Due to the characteristics of multi-tooth line contact, toroidal involute worm drive has the advantages of high bearing capacity and so on. However, due to increased constraints, it is more sensitive to manufacturing error and assembly error. To reduce the error sensitivity, this study proposes a modified toroidal involute worm drive based on the medium gear. The meshing geometry model between involute gears, medium gears and toroidal worms is constructed, and the local conjugate contact analysis method of space points of the drive pair is established. The spatial point-contact analysis method is developed, combined with numerical analysis and finite element simulation analysis, and the variation principles of meshing characteristics are revealed.The results show that the novel toroidal worm drive has lower error sensitivity, and can maintain the bearing capacity under high load. Based on a man-machine interactive heavy-duty robot rotary joint applied to 7 km automatic drilling rigs, a prototype of modified involute enveloping toroidal worm drive reducers is developed, and the correctness of theoretical analysis is verified.